Answer:
when x = -2, f(x) = 1/27
when x = -1, f(x) = 1/9
when x = 0, f(x) = 1/3
when x = 1, f(x) = 1
when x = 2, f(x) = 3
Step-by-step explanation:
Given:
![f(x)\text{ = 3}^(x-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5yeu4xdam9v8237n848auwggtvc8kam0kc.png)
To find:
to get the y values for x = -2, -1, 0, 1, and 2
To determine the corresponding values of f(x), we will substitute each of the values into the given function
![\begin{gathered} f(x)\text{ = 3}^(x-1) \\ when\text{ x = -2} \\ f(x)\text{ = 3}^(-2-1)\text{ = 3}^(-3) \\ f(x)\text{ = }(1)/(3^3)\text{ } \\ f(x)\text{ = }(1)/(27) \\ \\ when\text{ x = -1} \\ f(x)\text{ = 3}^(-1-1)\text{ = 3}^(-2) \\ f(x)\text{ = }(1)/(3^2) \\ f(x)\text{ = }(1)/(9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/fqob9pi0si8ns4i2xlnvjgqeyfl14914es.png)
![\begin{gathered} when\text{ x = 0} \\ f(x)\text{ = 3}^(0-1)\text{ = 3}^(-1) \\ f(x)\text{ = }(1)/(3^1) \\ f(x)\text{ = }(1)/(3) \\ \\ when\text{ x = 1} \\ f(x)\text{ = 3}^(1-1)\text{ = 3}^0 \\ f(x)\text{ = 1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/95tiyt9vtp1wyy97ijyp1kkwmcq10fzx8g.png)
![\begin{gathered} when\text{ x = 2} \\ f(x)\text{ = 3}^(2-1)\text{ = 3}^1 \\ f(x)\text{ = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/v3h3x9nvug9u924waiv74gle3ojr8o3lb4.png)